2010
DOI: 10.1371/journal.pone.0009479
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Clinical Trials Methodology Over Time: A Systematic Review of Six Decades of Research in Psychopharmacology

Abstract: BackgroundThere have been many changes in clinical trials methodology since the introduction of lithium and the beginning of the modern era of psychopharmacology in 1949. The nature and importance of these changes have not been fully addressed to date. As methodological flaws in trials can lead to false-negative or false-positive results, the objective of our study was to evaluate the impact of methodological changes in psychopharmacology clinical research over the past 60 years.Methodology/Principal FindingsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 123 publications
0
20
0
Order By: Relevance
“…Overall, trial duration ranged from 0.1 to 260 weeks (median [IQR] 12 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Only eight diabetes trials (6.6%) enrolled subjects with type 1 diabetes (numbers not shown in tables). Table 3 presents results for the distribution of trial characteristics by the study outcome.…”
Section: Trial Characteristics and Study Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Overall, trial duration ranged from 0.1 to 260 weeks (median [IQR] 12 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Only eight diabetes trials (6.6%) enrolled subjects with type 1 diabetes (numbers not shown in tables). Table 3 presents results for the distribution of trial characteristics by the study outcome.…”
Section: Trial Characteristics and Study Outcomementioning
confidence: 99%
“…These studies generally failed to quantify the number of placebo-only-controlled trials, distinguish the presence of an additional placebo control group in a multi-armed trial, or assess whether subjects in the placebo group were required to be given concomitant or background therapy. [24][25][26][27][28][29][30] To our knowledge, the extent to which placebo-only versus active interventions are provided to control group subjects in clinical trials has not been examined across multiple diseases. This study attempts to fill this gap by systematically assessing the distribution and characteristics of placebo-only versus active-controlled clinical trials supporting FDA approvals of new drugs and biologics for nine common life-threatening diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this issue can threaten internal validity by increasing effect sizes on all groups, but not necessarily diminish the generalizability of a NIBS-pharmacotherapy trial. Although a design with a placebo arm is methodologically sound, there is an important ethical concern: on one hand, placebo use has been ubiquitous in psychiatric research since the first controlled trials 60 years ago [25]; on the other hand, there is the risk of harming the principle of equipoise, which states that there should be 'genuine uncertainty' on the preferred treatment [26]. In fact, a recent meta-ana lysis demonstrated that pharmacological interventions and placebo present similar suicidal risk in short-term studies [27]; ethical committees usually demand that patients with severe suicidal ideation must not be enrolled in placebo trials, and that patients should be actively asked about suicidal thoughts throughout the trial, and be dropped-out if the suicidal risk is high.…”
Section: Placebo Responsementioning
confidence: 99%
“…In 1960s and 1970s there are reports of a method of non-invasive brain stimulation named "brain polarization", quite similar to modern transcranial direct current stimulation (tDCS), which could enhance mood and alertness in healthy volunteers 3 and treat depression 4,5 . Later on, this method was largely abandoned, possibly due to the advancement of psychopharmacology 6 and the social stigma of electroconvulsive therapy (ECT) that hindered the development of other forms of non-invasive brain stimulation.…”
Section: Introductionmentioning
confidence: 99%